An Educator’s Guide to Project-Based Learning: Turning Theory into Practice - Wahyuni, Sri; Hidayanto Pancoro Setyo Putro, Nur; Efendi, Anwar (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This review examines An Educator’s Guide to Project-Based Learning: Turning Theory into Practice by Fey Cole (Routledge, 2024), a timely contribution to the literature on student-centered pedagogy. The book introduces Project-Based Learning (PBL) as a transformative approach that integrates theoretical insights with practical strategies across diverse educational contexts, from early childhood to higher education. Organized into thirteen chapters, the text explores themes such as cultivating PBL culture, teacher professional growth, learning environments, scaffolding, and sustainable frameworks for practice. Case studies and illustrative examples make the book accessible and inspiring, particularly for educators seeking to foster creativity, collaboration, and authentic learning experiences. At the same time, the review highlights several underexplored areas. Structural constraints, including rigid curricula and limited resources, receive relatively brief attention, and the discussion could be enriched by more cross-cultural perspectives and non-Western examples. Despite these limitations, Cole convincingly positions PBL as a viable and transformative pedagogy capable of equipping learners with the skills, confidence, and agency required to thrive in the twenty-first century. This book will therefore be of value not only to teachers and practitioners but also to policymakers and educational leaders committed to advancing meaningful and sustainable learning.